Competition and Market Power in the Manufacturing Industries: A Comparative Study - Hadiseh Mohseni; Mosayeb Pahlavani; Mohhamad Nabi Shahiki Tash; Seyed Hossein Mirjalili (International Economics Studies, 2021)
This paper examines the gap between marginal cost and the price of 22 manufacturing industries in Iran at ISIC 2-digit level and 32 industries at a 3-digit level during 1995-2015 compared to selected countries. It examines the gap by using the Hall-Roeger model. We found that in garments, basic chemicals, non-metallic mining, and refined petroleum products, the price and marginal cost difference are high and in tobacco industries are low. In 3 out of 22 industries at ISIC 2- digit level and in 11 out of 32 industries at 3-digit level, Iranian industries have higher markups and a significant gap between price and marginal cost than Japan, Germany, France, and the United Kingdom. Also from 32 industries in ISIC 3-digit level and 22 industries in 2-digit level, Iran has the lowest mark-up in the tobacco industry with 1.03 and in chemical products with 2,33, has the highest markup.
Keywords: 330; Markup; Manufacturing Industries; Market Power; Marginal Cost; Iranian Economy